Cognitive dissonance and investors’ decision-making: A review - Fatima, Afreen (Goodwood Publishing, 2019)
Purpose: The purpose of this research is to develop a conceptual framework of cognitive dissonance bias that influences the investment decision-making. Research Methodology: This research uses empirical studies in order to assess the accurate deviation of investors’ behaviour from rational decisions. Results: The result of this study reveals the identified factors like age, emotional biases, overconfidence, and confirmations biases that enhance the cognitive dissonance that influence the decision making of the investors. Keywords: Cognitive dissonance bias, Psychological biases, Investment decisions, Behavioural finance, Psychology of investors. How to Cite: Fatima, A. (2019). Cognitive dissonance and investors decision-making: a review. International Journal of Financial, Accounting, and Management, 1(1), 39-45